Machine and learner interaction in programmed and computer-assisted instruction - Reid, Jackson B. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
One recent focus of attention of educational psychology researchers in PI and CAI at The University of Texas at Austin has been upon the area of interaction between the nature and conditions of instruction and the personality characteristics of the learner. Intellectual ability is revealed as one of the most important determinants of success regardless of the instructional medium employed, although there is some indication that the overriding influence of intelligence on learning can be minimized by CAI under certain optimal conditions. The influences of such personality constructs as “anxiety,” “neuroticism,” “dominance,” “submissiveness,” “attitude toward mechanized instruction,” etc. on success in learning are also reviewed. perform better alone at a CAI terminal, while those with different personality characteristics do better if working in cooperation with a partner. The spectacular development that has occurred in instructional technology is briefly outlined and contrasted with the paucity of experimentation that has been accomplished in an effort to comprehend the interaction between the nature of the learner and the conditions of the instructional situation. A pressing need for further investigation of this important interaction is deemed essential.